Eyeshield 21 - Inagaki, Riichiro; Murata, Yusuke, 1986-; Powell, Allison Markin (San Francisco, CA : Viz Media, 2005)
Fearful Sena Kobayakawa has been running away from bullies all his life, but when he puts on special football gear, he attains unbelievable speed that may just help him become a legendary high school football star.
v. 1. The boy with the golden legs -- v. 2. The false hero -- v. 3. And they're called the Devil Bats -- v. 4. Intimidation -- v. 5. Powerful -- v. 6. Devil Bats take flight -- v. 7. Musashi -- v. 8. True warriors seek out strong foes -- v. 9. Hell is for Devil Bats -- v. 10. Is there a loser in the house? -- v. 11. Open season -- v. 12. Devil Bat ghost -- v. 13. Who is the real Eyesheild 21? -- v. 14. The Demons vs. the Gods of the Sea -- v. 15. Tokyo's strongest player -- v. 16. The dawn of the time-out -- v. 17. The drive to be the best -- v. 18. Sena Kobayakawa -- v. 19. The successor -- v. 20. Devils vs. Gods -- v. 21. They were 11 -- v. 22. Time-out 0 -- v. 23. Then came showdown -- v. 24. The indomitable fortress -- v. 25. Perfect player -- v. 26. Rough 'n' tumble -- v. 27. Seijuro Shin vs. Sena Kobayakawa -- v. 28. Tokyo Dome of the decisive battle -- v. 29. The second quarterback -- v. 30. This is American football -- v. 31. And the winner is ... -- v. 32. Christmas Bowl -- v. 33. The devil's mistake -- v. 34. The last of the Deimon Devil Bats -- v. 35. The world is mine -- v. 36. Sena vs. Panther -- v. 37. Ready set hut.
"This book reads from right to left"--Page 4 of cover.
"First published in Tokyo, Japan in 2002 by Shueisha, Inc."--Title page verso.
"First printing: October, 2011"--T.p. verso, v. 37.
"Final volume!"--Page [4] of cover, v. 37.
"Rated T+ for older teens"--Page 4 of cover.
Translated from the Japanese.
Keywords: High school athletes -- Japan -- Humor -- Comic books, strips, etc; Football -- Japan -- Humor -- Comic books, strips, etc; Young men -- Japan -- Conduct of life -- Comic books, strips, etc; Graphic novels; Graphic novels; Young men -- Conduct of life; Japan; Graphic novels; Manga; Comic books, strips, etc